2020
DOI: 10.1101/2020.12.04.412320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ppard Is Essential in Acceleration of Pancreatic Ductal Adenocarcinoma Development by High-Fat Diet in MutantKrasMice

Abstract: Pro-obesity high-fat diet is linked with an increased incidence of pancreatic cancers, but the molecular underpinnings of this association remain poorly understood. Here, we report that PPARD is upregulated in pancreatic intraepithelial neoplasia lesions (PanINs) at early stages of pancreatic tumorigenesis in humans and mutant Kras mice. Transgenic overexpression of Ppard in pancreatic epithelial cells drastically accelerates the development and progression of pancreatic ductal adenocarcinoma in mutant Kras mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Finally, we found that genetic or pharmacological targeting of PPAR-δ inhibited tumor aggressiveness and metastasis in vitro and in vivo (Figure 8). These data are in line with previous reports for murine PDAC models showing that Ppard knock-down strongly decreased tumorigenesis mouse melanoma cells (Zuo et al, 2017), and Ppard knockout inhibited tumor progression in KC mice on a high-fat diet (Liu et al, 2020). Taken together, accumulating data now strongly support the concept that PPAR-δ inhibition reduces the MYC/PGC1A ratio and thereby diminishes PDAC progression and metastasis.…”
Section: Parejo-alonso Et Al Ppar-delta Drives a Pro-metastatic Metabolic Programsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, we found that genetic or pharmacological targeting of PPAR-δ inhibited tumor aggressiveness and metastasis in vitro and in vivo (Figure 8). These data are in line with previous reports for murine PDAC models showing that Ppard knock-down strongly decreased tumorigenesis mouse melanoma cells (Zuo et al, 2017), and Ppard knockout inhibited tumor progression in KC mice on a high-fat diet (Liu et al, 2020). Taken together, accumulating data now strongly support the concept that PPAR-δ inhibition reduces the MYC/PGC1A ratio and thereby diminishes PDAC progression and metastasis.…”
Section: Parejo-alonso Et Al Ppar-delta Drives a Pro-metastatic Metabolic Programsupporting
confidence: 91%
“…Even more importantly, poor patient outcome, including reduced metastasis-free survival correlated with PPARD expression in various cancer types (Abdollahi et al, 2007;Zuo et al, 2017). However, while accumulating evidence suggest that PPAR-δ also promotes tumor progression and metastasis in PDAC (Liu et al, 2020;Sanford-Crane et al, 2020;Zuo et al, 2017), other reports have questioned these finding (Coleman et al, 2013;Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%